Rehabilitative management of back pain in children: protocol for a mixed studies systematic review. Issue 10 (14th October 2020) - Cancelliere, Carol; Wong, Jessica J; Yu, Hainan; Mior, Silvano; Brunton, Ginny; Shearer, Heather M; Rudoler, David; Hestbæk, Lise; Papaconstantinou, Efrosini; Cedraschi, Christine; Swain, Michael; Connell, Gaelan; et al.
Abstract : Introduction: Little is known about effective, efficient and acceptable management of back pain in children. A comprehensive and updated evidence synthesis can help to inform clinical practice. Objective: To inform clinical practice, we aim to conduct a systematic review of the literature and synthesise the evidence regarding effective, cost–effective and safe rehabilitation interventions for children with back pain to improve their functioning and other health outcomes. Methods and analysis: We will search MEDLINE, Embase, PsycINFO, CINAHL, the Index to Chiropractic Literature, the Cochrane Controlled Register of Trials and EconLit for primary studies published from inception in all languages. We will include quantitative studies (randomised controlled trials, cohort and case–control studies), qualitative studies, mixed-methods studies and full economic evaluations. To augment our search of the bibliographic electronic databases, we will search reference lists of included studies and relevant systematic reviews, the WHO International Clinical Trials Registry Platform and consult with content experts. We will assess the risk of bias using appropriate critical appraisal tools. We will extract data about study and participant characteristics, intervention type and comparators, context and setting, outcomes, themes and methodological quality assessment. We will use a sequential approach at the review level to integrate data from the quantitative, qualitative and economic evidence syntheses. Ethics and dissemination: Ethics approval is not required. We will disseminate findings through activities, including (1) presentations in national and international conferences; (2) meetings with national and international decision makers; (3) publications in peer-reviewed journals and (4) posts on organisational websites and social media. PROSPERO registration number: CRD42019135009.